Young people's preferences for HIV self-testing services in Nigeria: a qualitative analysis - Chisom Obiezu-Umeh; Titilola Gbajabiamila; Oliver Ezechi; Ucheoma Nwaozuru; Jason J. Ong; Ifeoma Idigbe; David Oladele; Adesola Z. Musa; Florida Uzoaru; Collins Airhihenbuwa; Joseph D. Tucker; Juliet Iwelunmor (BMC, 2021)
Abstract Background HIV self-testing (HIVST) provides young people with a convenient, discreet, and empowering way to know their HIV status. However, there is limited knowledge of young people's preferences for HIVST services and potential factors that may influence the uptake of HIVST among this population. The purpose of this research was to use qualitative methods to examine HIVST preferences among Nigerian youth. Methods Semi-structured in-depth interviews with a purposive sample of young people 14-24 years old were conducted in Lagos, Nigeria. Data were analyzed thematically to identify themes and domains related to preferences and factors influencing the use of HIV self-testing. Results A total of 65 youth with mean age of 21 years, were interviewed, and the majority were females (56%). Four themes emerged as the most important characteristics that may influence young people's preferences for HIV self-testing: 1) Cost (i.e. majority of participants noted that they would pay between NGN500 to NGN1,500 naira (USD1.38-USD4.16) for oral HIV self-testing kits); 2) Testing method (i.e. although blood-based sample kits were more popular than oral-based self-testing kits, most preferred the oral-based option due to its perceived benefits and for some, phobia of needles); 3) Access location (i.e. participants suggested they preferred to obtain the HIVST kits from youth-friendly centers, pharmacies, private health facilities, and online stores); and 4) Continuing care and support (i.e. participants highlighted the importance of linkage to care with trained youth health workers for positive or negative test results or toll-free helpline). Conclusion HIV self-testing preferences among Nigerian youth appear to be influenced by several factors including lower cost, less invasive testing method, location of testing, and linkage to care and support post testing. Findings underscore the need to address young people's HIV self-testing preferences as a foundation for implementing programs and research to increase the uptake of HIVST.